2015 IEEE International WIE Conference on Electrical and Computer Engineering (WIECON-ECE) 2015
DOI: 10.1109/wiecon-ece.2015.7443980
|View full text |Cite
|
Sign up to set email alerts
|

Defected core hybrid cladding photonic crystal fiber with high birefringence & highly negative dispersion properties

Abstract: This paper presents a Defected Core Hybrid Cladding photonic crystal fiber with extremely high birefringence and highly negative dispersion properties at telecommunication window. This photonic crystal fiber (PCF) with a defected core having intentionally introduced walls of elliptical air holes is analyzed with full-vectorial finite element method(FEM).The proposed structure exhibits an extremely high birefringence (4.39×10-2) at operating wavelength 1550nm which is the highest to date and is particularly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Different types of PCF structures were suggested in order to overcome the weak confinement of light in the fiber core. For example, Shawkat et al proposed a PCF with a defected core and hybrid cladding to get a birefringence of 4.39 × 10 −2 [19]. Chen et al reported high birefringence of 1.5 × 10 −2 by arranging a core of elliptical air holes and a cladding of circular air holes in a hexagonal lattice [10].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of PCF structures were suggested in order to overcome the weak confinement of light in the fiber core. For example, Shawkat et al proposed a PCF with a defected core and hybrid cladding to get a birefringence of 4.39 × 10 −2 [19]. Chen et al reported high birefringence of 1.5 × 10 −2 by arranging a core of elliptical air holes and a cladding of circular air holes in a hexagonal lattice [10].…”
Section: Introductionmentioning
confidence: 99%